Chronology of the sedimentary processes during the postglacial sea level rise in two estuaries of the Algarve coast, Southern Portugal - Boski, T. (2013)
Four profiles of estuarine sediments obtained from boreholes drilled in the Algarve, Southern Portugal were studied in order to reconstruct the process of sediment accumulation driven by the postglacial sea level rise. In addition to the sedimentological analysis, the Foraminifera Index of Marine Influence (FIMI) permitted assessment of the nature and organization of sedimentary facies in the BelicheeGuadiana and Gilão-Almargem estuaries. The Beliche- Guadiana CM5 and Almargem G2 profiles accumulated in a sheltered environment, with the former presenting an almost continuous record of the sea level rise since ca 13 000 cal yr BP. The G1 and G3 profiles from the Gilão-Almargem area represent a more discontinuous record of the last 8000 years, which accumulated in the more dynamic environment of an outer estuary. The integration of all radiocarbon ages of dated levels, led to an estimate of sediment accumulation rates. Assuming a constant position of the sediment surface with respect to the tidal range and a negligible compaction of sediment, the sea level rose at the rate of 7 mm yr ^-1 in the period from 13 000 to 7500 cal yr BP. This process slowed down to ca 0.9 mm yr 1 from 7500 cal yr BP until the present. The marked historical change in the rate of sediment accumulation in these estuaries also occurred with the accumulation of organic matter and is, therefore, important data for global biogeochemical models of carbon. The main obstacle to obtain higher temporal resolution of the sedimentary processes was the intense anaerobic respiration of organic matter via sulphate reduction, which did not allow any accumulation of peat and, furthermore, led to erasure of the palaeontological record by acid formed from the subsequent oxidation of sulphides.